Genesis of hydrothermal gold mineralization in the Qianhe deposit, central China: Constraints from in situ sulphur isotope and trace elements of pyrite. (15th February 2021) - Feng, Jia‐Ying; Tang, Li; Santosh, M.; Zhang, Shou‐Ting; Sheng, Yuan‐Ming; Hu, Xin‐Kai; Wang, Liang
Abstract : The Qianhe gold deposit, located at Xiong'ershan in Eastern Qinling, with estimated gold reserves of 22 tons, hosts six orebodies within auriferous quartz veins and hydrothermally‐altered rocks along E–W trending faults. Here we present results from an integrated study involving field investigation, ore petrology, in situ sulphur isotopes, and trace elements analysis of gold‐bearing pyrite with a view to understanding the genesis of the hydrothermal gold mineralization. Three generations of pyrite are identified in the Qianhe Au deposit: Py1 is composed of coarse‐grained, euhedral cubic grains occurring at the margin of stage I quartz + pyrite vein; Py2 is occurs as porous grains coexisting with other sulphide minerals in stage II quartz + polymetallic sulphide veins; and Py3 is mainly composed of anhedral grains in stage III quartz + calcite + fluorite vein. Among the three generations, Py2 has the highest contents of Au (mean = 3.5 ppm), Ag (mean = 46.0 ppm), Zn (mean = 303 ppm), and Cu (mean = 346 ppm). The distribution and concentration of these trace elements are likely to be controlled by micro/nano‐inclusions in pyrite. The Co/Ni ratios range from 0.010 to 296, with most values lying between 0.1 and 10. The δ 34 S values of the various pyrite generations show a wide range between −17.9‰ and 4.5‰ with obviously higher values in Py3 (2.0‰ to 4.5‰) than those in Py1 (−16.7‰ to −13.5‰) and Py2 (−17.9‰ to −9.0‰). The negative δ 34 S values in Py1 and Py2 possibly resulted from sulphur isotope fractionation between sulphide and sulphate minerals. As sulphate minerals are absent in stage III, the slightly positive δ 34 S values in Py3 suggest a mixed source from mantle‐derived material and wall rocks of the Xiong'er Group. We correlate the genesis of gold mineralization in the Qianhe deposit with the extension and lithospheric thinning during Early Cretaceous, when ore‐bearing fluids channelled along fault zones induced hydrothermal alteration and Au mineralization. Abstract : Three generations of pyrite are identified in the Qianhe Au deposit, including coarse‐grained euhedral pyrite (Py1) occurring in the margin of the stage I quartz + pyrite vein; porous pyrite (Py2) coexisting with other sulphide minerals in the stage II quartz + polymetallic sulfide vein; and anhedral pyrite (Py3) in stage III quartz + calcite + fluorite vein. The trace elements entered the pyrite through two mechanisms in the Qianhe deposit; Co, Ni, As, Se, and Sb replace Fe and S in the pyrite in the form of isomorphism; whereas the economic metals (Au, Ag, Pb, and Zn) occur as micro‐ to nano‐sized mineral inclusion of galena, sphalerite, silver, gold, and electrum. The sulphur source of Qianhe Au deposit overprints the signature of precursor magma which was originated from mantle‐derived components and partially melted Taihua Group crustal components. The hydrothermal system in Qianhe Au deposit was mainly generated from post‐magmatic fluids. The Early Cretaceous magmatism, accompanied with lithospheric thinning and asthenosphere upwelling, introduced Au into the hydrothermal system from mantle sources.